Gender Quotas on Corporate Boards: Similarities and Differences in Quota Scenarios. Issue 3 (7th January 2020) - Mensi‐Klarbach, Heike; Seierstad, Cathrine
Abstract : In this article, the use of gender quotas to strengthen gender equality on corporate boards is explored. Examining national practices in ten European countries we provide an overview, categorizing the design of various corporate board quotas (CBQs) and the contexts in which they are embedded. In particular, similarities and differences along two dimensions are investigated: the design of the CBQs in terms of their hardness and progressiveness, and the institutional context in which they are embedded. From patterns of design and context configurations, different quota scenarios are discerned. We advance the discussion of female representation and the strategies of corporate boards beyond the rather misleading dichotomy of voluntary targets versus mandatory quotas, proposing a framework for understanding various CBQ designs. Moreover, we suggest that the configuration of design and institutional context, resulting in different quota scenarios affects female representation on corporate boards .